HISTORY OF PONTIANAK MUJAHIDIN EDUCATION FOUNDATION - Nunik Esti Utami; Muhammad Sadikin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2019)
The process of Islamization and the development of Islam in Indonesia has brought influence to the minds of the people. The influence is always developing not only limited to the mental spiritual field, but also in the form of the mindset and creativity carried out by the community. One form of this influence is the emergence of Islamic building art. First of all there was a mosque building which was one of the manifestations of Islamic culture. Then buildings that are non-religious appear as facilities that accommodate human needs. Palaces, palaces, castles, fortress buildings, and cemeteries. The Pontianak Mujahidin College, preceded by the Mujahidin Foundation in 1953, was also established by the Pontianak Great Mujahidin Mosque. Masjid Raya Mujahidin is an institution of Da'wah, BMT, Cooperatives, and educational institutions, namely the Pontianak Mujahidin College. This college was officially founded in 1980. The method used in this study is a descriptive qualitative research method in which data collection is human instrument, ie researchers act as data collectors. The analysis used uses intractive analysis. The results of this study are the first educational institutions established in junior high, high school, then kindergarten, elementary school, Madrasah Aliyah and Tsanwiyah. This college is growing rapidly along with the changing times. In addition, this college is one of the favorite Islamic educational institutions in the city of Pontianak. In addition to the good quality of education, it is also due to its strategic location on Jalan Ahmad Yani or a complex with the Pontianak Great Mujahidin Mosque.